Sport, age, and sex specific incidence of sports injuries in Western Australia. Issue 3 (1st June 2000) - Stevenson, Mark R; Hamer, Peter; Finch, Caroline F; Elliot, Bruce; Kresnow, Marcie-jo
Abstract : Objective —To describe the trends in recreational sports injury in Perth, Western Australia. Design —A prospective cohort study of sports injuries during the 1997 winter season (May to September). Setting —Sample of Australian football, field hockey, basketball, and netball players from the Perth metropolitan area, Western Australia. Methods —A cohort of sports participants was followed over the five month winter sports season. Before the season, participants completed a baseline questionnaire and during the season were interviewed every four weeks by telephone. Results —Overall, 92% of participants (n = 1391) who completed a baseline questionnaire completed at least one follow up telephone interview. About half (51%) of the cohort sustained one or more injuries during the winter season accounting for a total of 1034 injuries. Most injuries were of moderate (58%, n = 598) or minor (40%, n = 412) severity, with only 3% (n = 24) requiring emergency department treatment or a hospital stay. The injury incidence rate was greatest for football (20.3/1000 hours of participation), similar for field hockey and basketball (15.2/1000 hours and 15.1/1000 hours respectively), and lowest for netball (12.1/1000 hours). The incidence of injury was greatest in the first four weeks of the season, and participants aged between 26 and 30 years had about a 55% greater risk of injury than those aged less than 18 years. Conclusions —This is one of the first studies to show that recreational sports are safe. Although the likelihood of injury was greatest in the first month of the season, few injuries required admission to hospital or emergency department treatment. A greater emphasis on prevention in the early part of the season should help to reduce the elevated incidence of injury found at this time.